The Effect Of Advertising And Store Atmosphereon The Purchase Decision Ondialog Coffee Deli Serdang - Irwansyah Putra; Audrey Faiq Sabillah (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to determine whether Advertising and Store Atmosphere have an influence on Purchase Decisions at Dialog Coffee Deli Serdang. The population used in this study were all customers of Dialog Coffee. This study used a sample of 95 respondents, using accidental sampling as a sampling technique. Hypothesis testing in this study uses statistical model analysis consisting of validity test, reliability test, classical assumption test, multiple linear regression, F test, t test, and coefficient of determination (R2) using SPSS 25.00 software (Statistical Product and Services Solution). for windows. Research data sourced from primary data and the process of collecting data and using a questionnaire. The results showed that there was a relationship between the independent variable, namely Advertising and Store Atmosphere, on the dependent variable, namely Purchase Decision. The Advertising variable, the value of t is tcount > ttable (7.262 > 1.986), with a significance level of 0.000 < 0.05 and for the Store Atmosphere variable, the value of t tcount > ttable (3.351> 1.986) with a significance level of 0.001 < 0.05 can be obtained. concluded that Advertising and Store Atmosphere have a positive and significant impact on Purchase Decisions at Dialog Coffe. And the F test obtained fcount > ftable (82.758 > 2.36) with a significance level of 0.000 < 005 so it can be concluded that Advertising (X1) and Store Atmosphere (X2) simultaneously have a positive and significant effect on Purchase Decisions (Y) at Dialog Coffee.